Defining the Buyer Persona and Presenting Its Use for Marketing Purposes for Effective Communication - Vida, Noémi; Bringye , Bernadett; Varga, Erika; Máté, Balázs (Acta Carolus Robertus, 2024)
The origin of buyer persona modeling is software development, but today this methodology is used in a wide variety of fields, including marketing and communication process planning. Buyer personas incarnate buyers, they are person descriptions that represent fictitious characters, but are based on real data. A picture and a name are usually associated to the description of buyer personas, to facilitate the identification of decision makers with them. The essence of the methodology is to involve effectively the needs of users and customers in the various decision-making processes. Although buyer persona modeling has many similarities with segmentation, it goes far beyond it, the reason being that it does not focus only on demographic data, but on the behavior and motivation of users. If used properly, it can be a very effective tool for making marketing processes more efficient. However, buyer personas also have many criticisms. Several experts stated that the methodology is not empirically supported. Below, we present the methodology used to model buyer personas, and their application in the marketing field. In our article, we also discuss the criticism of buyer personas.
Keywords: buyer persona; online marketing; market segmentation